Metaphorical Study on Health Management and Nutrition and Dietetics Students' Perceptions of Strategy - Gamze Aydın Toprak (Sağlık ve Hemşirelik Yönetimi Dergisi)
Aim: The aim of this research is to examine the perceptions of Health Management and Nutrition and Dietetics Department students regarding the concept of strategy through metaphors. Method: A total of 91 students studying in the fall semester of the 2022-2023 academic year in two different undergraduate programs of a foundation university participated in the research. The data of the research was obtained by completing the sentence 'Strategy is like… because,…' Phenomenological analysis, one of the qualitative research methods, was preferred in the analysis of the data. The MAXQDA 2020 program was used in the analysis and visualization of the data. Results: As a result of the research, it was seen that the students expressed the concept of strategy with quite a variety of metaphors. 64 different metaphors were developed, and these metaphors were grouped under 11 different categories. The category where metaphors were most concentrated is the game category. Students mostly compared strategy to chess, road and life concepts. Conclusion: It was concluded that the students participating in the research saw strategy as a kind of game that is created in the mind, guides institutions and requires them to use their competencies. It is thought that the results obtained regarding the perception of strategy will guide managers working in the health sector, human resources specialists and researchers working in the field in terms of developing training programs and developing more effective strategy applications in organizations.